Signaling network analysis reveals fostamatinib as a potential drug to control platelet hyperactivation during SARS-CoV-2 infection - Osmanoglu, Özge; Gupta, Shishir K.; Almasi, Anna; Yagci, Seray; Srivastava, Mugdha; Araujo, Gabriel H. M.; Nagy, Zoltan; Balkenhol, Johannes; Dandekar, Thomas (Frontiers in Immunology, 2023)
Dysregulated pro-thrombotic events are one of the prevalent causes of intensive care unit (ICU) admissions of COVID-19 patients, although the signaling events in the stimulated platelets are still unclear. We compared public transcriptome data of platelets from healthy donors, ICU, and non-ICU COVID-19 patients. To go beyond earlier analyses, we modeled involved networks and control cascades with the integration of a global human signaling network and transcriptome data. We investigated the control of platelet hyperactivation and involved proteins. We demonstrate that the network control in ICU patients must be much higher than in non-ICU patients. For controlling platelets' hyperactivity, non-ICU patients require fewer proteins to be controlled than ICU patients. Identifying indispensable proteins for signal transmission reveals key subnetworks that can be targeted for system control in COVID-19 related platelet hyperactivity. We scrutinized FDA approved drugs for targeting the proteins that are indispensable for platelet control and simulated their effects on platelet activity in ICU patients. These network analyses support fostamatinib as a strong drug to prevent thrombosis in COVID-19 patients. We demonstrate further, how SARS-CoV-2 efficiently affects host platelets by targeting indispensable and critical proteins for platelet activity control. Our findings uncovered signaling involved in SARS-CoV-2 infected platelet hyperactivation. We evaluate several drugs that can be used to specifically control platelet hyperactivity in ICU patients suffering from this general type of platelet hyperactivation including septic patients. Our approach focuses on repurposing existing drugs, originally used for various conditions, to gain optimal control over the signaling network responsible for platelet hyperactivity in COVID-19 patients. Our analysis provides specific pharmacological recommendations for treatment, with drug prioritization varying depending on the patient's condition, aligning with the distinct network states observed in each condition. Interactive networks and results can all be found at https://fostamatinib.bioinfo-wuerz.de/.